2018
DOI: 10.1177/1741143218775428
|View full text |Cite
|
Sign up to set email alerts
|

Linking school-based management and school effectiveness: The influence of self-based management, motivation and effectiveness in the Arab education system in Israel

Abstract: Using a sample of 300 Arab teachers in Israel, we developed a model to analyze how school-based management directly and indirectly (through motivation) affects school effectiveness. The results show that there is a positive relationship between all dimensions of self-management (decision-making, resource and personnel management, availability of resources, and organizational structure) and school effectiveness. In addition, the results show full mediation between resource management, personnel and organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
1
24
0
3
Order By: Relevance
“…However, based on research by Liantos & Pamatmat [23], TQM implementation, in general, influences school leadership because TQM practices have a relationship with staff development and school leadership in carrying out its role in SG. With the existence of SG practices, the principal's decision-making authority, school decision-making [68], as well as school board involvement can emerge to be able to create a better teaching and learning environment and student academic achievement that are indicators of effective schools [10,45]. By combining the results of these studies it was implied that TQM had a role in creating the application of SG which could ultimately increase school effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, based on research by Liantos & Pamatmat [23], TQM implementation, in general, influences school leadership because TQM practices have a relationship with staff development and school leadership in carrying out its role in SG. With the existence of SG practices, the principal's decision-making authority, school decision-making [68], as well as school board involvement can emerge to be able to create a better teaching and learning environment and student academic achievement that are indicators of effective schools [10,45]. By combining the results of these studies it was implied that TQM had a role in creating the application of SG which could ultimately increase school effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Arar and Nasra's research [68] revealed that there is a positive relationship between SG and school effectiveness. According to him, with the SG practice, the principal's decisionmaking authority, school decision-making, and the involvement of the school board could emerge to be able to create a better teaching and learning environment and student academic achievement.…”
Section:  Issn: 2252-8822mentioning
confidence: 94%
“…To measure the effectiveness of a school, a systematic approach is needed that involves many key factors such as managerial function, individuals' performances, ethics, level of trust, culture and climate of schools, parental involvement, teachers' performances and their job satisfaction (Ostroff& Schmitt, 1993, as cite by Uline, Miller & Tschannen-Moran, 1998). Arar and Nasra (2018) summarized the definition of effective school in the educational literature in four facets: (a) the output goal approach, which claims that an effective school is a school whose achievements are above those that can be expected under defined prediction conditions; (b) the goal approach, according to which a school is effective if it achieves the goals it sets for itself within a defined period of time; (c) the resource approach, according to which a school is considered effective if it can mobilize the necessary resources to fulfill its tasks; (d) the internal processes approach, by which a school is considered effective if its functioning is smooth and its organizational climate is healthy; (e) the stakeholders' satisfaction approach, according to which an effective school is defined as a school that meets the expectations and needs of the stakeholders (parents, students, and the community); and (f) the combined approach, by which an effective school is an educational institution that works systematically and continuously for self-improvement in order to achieve its goals by maximizing its physical and human resources while maintaining the well-being of teachers and students. Hallinger and Heck (2011) determine five characteristics of an effective school: developing high expectations of students and teachers, order, discipline, emphasis on student-centered activities, and monitoring students and teachers work and strong leadership of the school principal.…”
Section: Effective Schoolsmentioning
confidence: 99%
“…School-Based Management (SBM) serves as a new paradigm in education management; a package of educational reform in maintaining a balance of authority between the government and the school children, as well as an autonomous decision-making centre (Arar & Nasra, 2018;Bandur, 2017;Tansiri & Bong, 2018). In the education system, the level of decision making can be determined through the extent of autonomy by the school to be able to make decisions regarding curriculum, staff, and strategic planning processes (Alyami & Floyd, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of SBM implementation has shown positive outcomes in various aspects of the school including student attendance, academic achievement and school management (Arar & Nasra, 2018;Bandur, 2012;Barrera-osorio et al, 2009;Caldwell, 2005;Grauwe, 2005;World Bank, 2013). For example, SBM in the Philippines has resulted in improved school performance within three years (2006)(2007)(2008)(2009) of implementation (World Bank, 2013) while in Indonesia, a significantly positive effect on student learning outcomes since it was started implemented in 2002 (Chen, 2019).…”
Section: Introductionmentioning
confidence: 99%